Analysis of borehole stability in gas drilling using a thermal elastoplastic coupling model. Issue 12 (10th October 2021) - Zhu, Zhongxi; Wang, Chaofei; Ye, Yuchen; Lei, Wanneng
Abstract: Gas drilling causes lower pressure in the borehole and the Joule‐Thomson effect to occur at the bit nozzle, resulting in a temperature distribution in the borehole different from that in the original formation. The borehole temperature is far lower than the original formation temperature near the bottom of the borehole. This temperature difference leads to thermal stress on the borehole. The borehole temperature is higher than the formation temperature in the upper part of the borehole, causing the surrounding rock to expand because of the resulting thermal stress, which enhances the expansion of the surrounding rock into the borehole. The force supporting the borehole wall is thus weaker, and the borehole inevitably deforms under the original in situ stress. Meanwhile, the complete stress‐strain process of rock can be simplified into three linear stages: elasticity, plasticity, and residual. According to the combination of the Tresca yield criterion and the thermal stress, a thermal elastoplastic coupling model was developed to calculate the radii of the plastic softening and broken zones. An example calculation showed that the shrunken thermal stress at the bottom of the borehole could enhance the stability of the borehole wall, while the expansive thermal stress at the top could increase the instability of the borehole. When thermal stress was considered, the thermal elastoplastic model of rock was more consistent with the field measurements than when it was neglected.